The Pacific Exposition: Indonesia's Hybrid Diplomacy Arena in State Rationality and Bureaucratic Politics in the Southwest Pacific - Hastira, Muhammad Fajhriyadi (Department of International Relations, Hasanuddin University, 2026)
This study aims to analyze the dynamics of Indonesia's foreign policy decision-making by implementing the Pacific Exposition as an instrument of hybrid diplomacy, namely economic and political diplomacy in the Pacific region. This phenomenon is important because, in addition to opening access to non-traditional export markets, the expo defuses the Papua issue and strengthens Indonesia's nation branding. Using a qualitative approach and case study design, this study examines the 2019 and 2021 expos as units of analysis. Data were obtained from official government documents, diplomatic speeches, academic publications, international organization reports, and interviews with key actors from the Ministry of Foreign Affairs and the Ministry of Trade. The analysis used process tracing techniques to trace the cause-and-effect relationships in the policy formulation process. The results show that the decision to hold the expo was born out of the state's rational calculation to restore the post-pandemic economy as well as a political strategy to address the Papua issue, but the tug-of-war between bureaucratic interests and the role of informal networks influenced its implementation. These findings expand the application of Foreign Policy Analysis in the Indonesian context by combining the Rational Actor Model and the Bureaucratic Politics Model, and provide practical implications for strengthening bureaucratic coordination in economic diplomacy. This study recommends the institutionalization of expos as a regular agenda and further study on the role of informal politics in Indonesian diplomacy.